Sociodrama-based group guidance to enhance students' self-awareness regarding digital device use: a pre-experimental study - Hany Noer Nadhifa; Arri Handayani; Siti Fitriana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Excessive digital device use among students has become an important educational concern because it may negatively affect learning activities, social interactions, and time management. This study aimed to examine the potential effectiveness of group guidance using the sociodrama technique in enhancing students' self-awareness regarding digital device use. A quantitative pre-experimental study employing a one-group pretest–posttest design was conducted with ten students selected through purposive sampling based on their low levels of self-awareness regarding digital device use. Data were collected using a 24-item self-awareness questionnaire with acceptable reliability (Cronbach's α = 0.788). The intervention consisted of five group guidance sessions using the sociodrama technique. Data were analyzed using the Shapiro–Wilk normality test followed by a paired-samples t-test. The findings indicated that students' mean self-awareness score increased following the intervention, and the improvement was statistically significant (p < .001) with a very large effect size (Cohen's d = 2.70). These findings provide preliminary evidence that group guidance using the sociodrama technique may enhance students' self-awareness regarding digital device use. However, because this study employed a pre-experimental design without a comparison group and involved a relatively small sample, the findings should be interpreted with caution. Further studies using more rigorous experimental designs and larger samples are recommended to confirm the effectiveness of the intervention.